Catalytic Enantioselective Synthesis of Mariline A and Related Isoindolinones through a Biomimetic Approach. Issue 48 (2nd November 2017) - Min, Chang; Lin, Yingfu; Seidel, Daniel
Abstract: The catalytic enantioselective synthesis of isoindolinones was achieved through the condensation of 2‐acyl‐benzaldehydes and anilines. In the presence of 1 mol % of a chiral phosphoric acid catalyst, reactions reach completion within 10 min and provide products with up to 98 % ee . Anilines with an ortho t ‐butyl group form atropisomeric products, thereby enabling the simultaneous generation of axial and point chirality from two achiral substrates. This method was applied to the first synthesis of mariline A. Abstract : Give me a ring : The catalytic enantioselective synthesis of isoindolinones was achieved through the condensation of 2‐acylbenzaldehydes and anilines. In the presence of 1 mol % of a chiral phosphoric acid catalyst, reactions reach completion within 10 minutes and provide products with up to 98 % ee . Anilines with an ortho t ‐butyl group form atropisomeric products. This method was applied to the first synthesis of mariline A.